Apparatus for centrifuge modelling of twin-tunnel construction. Issue 3 (September 2012) - Divall, Sam; Goodey, Richard James
Abstract : In urban areas it is common for pairs of tunnels to be used as a method for building rapid transit systems. Driven by an increasing population and demand for services, tunnels are more widespread in their use than at any previous time. Construction of any form of tunnel causes ground movements which have the potential to damage existing surface and sub-surface structures. Modern tunnelling practice aims to reduce these movements to a minimum but there is still a requirement for accurate assessments of possible damage to structures resulting from settlements. For tunnels driven in clay, superposition of settlement predictions made by considering a single tunnel is an accepted method used to estimate movements around pairs of tunnels. Previous research, particularly numerical studies, has indicated that this may not necessarily be sufficient. In this paper a series of centrifuge model tests designed to investigate settlements related to twin-tunnel construction are described. The development of the experimental apparatus for sequential twin-tunnel construction with variable centre-to-centre spacing and volume loss is described in detail.